2005
DOI: 10.4049/jimmunol.174.11.7147
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ Regulatory T Cells Restrain Pathogenic Responses during Leishmania amazonensis Infection

Abstract: Although activation of CD4+ T cells mediates pathogenesis in Leishmania amazonensis (La)-infected mice, these susceptible mice do not develop a polarized Th2 response, suggesting a unique mechanism of disease susceptibility. To understand how Th cell activities are regulated, we examined the frequency and phenotypes of regulatory T (Treg) cells. At 1–3 wk of infection, relatively high percentages of CD4+CD25+CD86+ T cells, as well as high levels of FoxP3, TGF-β1, and IL-10RI transcripts, were detected in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 55 publications
7
84
0
2
Order By: Relevance
“…In accordance with these reports, we also observed a higher proliferation of CD4 + and CD8 + effector T cells and increased IFN-γ levels in paws from infected P2X7 KO mice. This excessive T cell proliferation might contribute to the pathogenesis in leishmaniasis because CD4 + T cells have a pathogenic role [18], while regulatory T cells have a protective role in this disease [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with these reports, we also observed a higher proliferation of CD4 + and CD8 + effector T cells and increased IFN-γ levels in paws from infected P2X7 KO mice. This excessive T cell proliferation might contribute to the pathogenesis in leishmaniasis because CD4 + T cells have a pathogenic role [18], while regulatory T cells have a protective role in this disease [19].…”
Section: Discussionmentioning
confidence: 99%
“…The Th1/Th2 dichotomy is not observed in L. amazonensis infection because a mixed frequency of CD4 + T cells producing IFN-γ and IL-4 is found during the infection [17]. Interestingly, effector CD4 + T cells are associated with disease pathology [18], while regulatory T cells are associated with lesion resolution [19].…”
Section: Introductionmentioning
confidence: 99%
“…For detection of intracellular cytokines, DLN cells (1 x 10 6 /ml) were re-stimulated with phorbol myristate acetate (PMA)/ionomycin in the presence of GolgiPlug™ (BD Biosciences) for 6 h. Subsequently, cells were stained for surface antigens, fixed/permeabilized with a Cytofix/Cytoperm solution (BD Biosciences), and then incubated for 20 min with PEconjugated rat anti-mouse IL-10 (JES5-16E3, eBioscience) and FITC-conjugated rat antimouse IFN-γ (XMG1.2, eBioscience). For the analysis of lesion-derived CD4 + T cells, tissues of infected mice were processed as previously described (Ji et al, 2005), with some modifications. Briefly, the soft foot tissue of 3-week infected mice were harvested, cut and torn into small pieces by forceps.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…In addition, in a model of CCL due to infection with L. major, it has been shown that Treg cells accumulate at the site of infection, rendering the Th1 response induced by infection with the L. major Sd strain ineffective (1). Treg cells were also shown to limit immunopathogenesis caused by L. amazonensis by inhibiting the activities of L. amazonensis-specific effector cells (17). In contrast, in a murine model of infection with L. mexicana, it was recently demonstrated that depletion of CD4 ϩ…”
mentioning
confidence: 99%